2020
DOI: 10.1186/s12935-020-1163-9
|View full text |Cite
|
Sign up to set email alerts
|

M2 bone marrow-derived macrophage-derived exosomes shuffle microRNA-21 to accelerate immune escape of glioma by modulating PEG3

Abstract: Background: Growing studies have focused on the role of microRNA-21 (miR-21) in glioma, thus our objective was to discuss the effect of M2 bone marrow-derived macrophage (BMDM)-derived exosomes (BMDM-Exos) shuffle miR-21 on biological functions of glioma cells by regulating paternally expressed gene 3 (PEG3). Methods: Seventy-one cases of human glioma tissues and 30 cases of non-tumor normal brain tissues were collected and stored in liquid nitrogen. PEG3 and miR-21 expression in glioma tissues was tested. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 41 publications
0
37
0
Order By: Relevance
“…Additionally, ZNF667-AS1 can competitively bind to miR-93-3p, which targets PEG3, to regulate the progression of CC [ 31 ]. Recent research has shown that inhibiting PEG3 would promote the immune escape of cancer cells [ 32 ]. BZRAP1-AS1 was found to be a novel biomarker associated with prostate cancer (PC), being downregulated in PC samples [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, ZNF667-AS1 can competitively bind to miR-93-3p, which targets PEG3, to regulate the progression of CC [ 31 ]. Recent research has shown that inhibiting PEG3 would promote the immune escape of cancer cells [ 32 ]. BZRAP1-AS1 was found to be a novel biomarker associated with prostate cancer (PC), being downregulated in PC samples [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…TAMs suppress the CD8 + T cell response to cancer by secreting immunosuppressive factors, including CCL5, CCL17, and CCL22. 132 In addition to these chemokines, Yang et al 133 found that M2-BMDM-derived exosomes (BMDM-Exos) shuttle miR-21 to promote migration, proliferation, and invasion, and inhibit the apoptosis of glioma cells by reducing the expression of paternally expressed gene 3 (PEG3). More importantly, this work provided evidence that BMDM-Exos can reduce the percentage of CD8 + T cells and inhibit the extent of cell cytotoxicity by accelerating the immune escape of gliomas and enhancing their progression.…”
Section: Macrophage-derived Exosomes Are Involved In Tumor Progressiomentioning
confidence: 99%
“…Additionally, ZNF667-AS1 can competitively bind to miR-93-3p, which targets PEG3, to regulate the progression of CC [31]. Recent research has shown that inhibiting PEG3 would promote the immune escape of cancer cells [32]. BZRAP1-AS1 was found to be a novel biomarker associated with prostate cancer(PC), being down-regulated in PC samples [33].…”
Section: Discussionmentioning
confidence: 99%